Tobacco use among Latinx adolescents: exploring the immigrant paradox - Anna E. Epperson; Jan L. Wallander; Marc N. Elliott; Mark A. Schuster (BMC, 2018)
Abstract Background Research suggests that an immigrant paradox exists where those who were not born in the United States (1st generation) have significantly better health than those who were born in the U.S. (2nd generation or more). The aim of the current study was to examine the immigrant paradox with respect to tobacco-related perceptions and parenting influences in smoking initiation among Latinx adolescents. Methods Data came from the 7th and 10th grade Healthy Passages™ assessments of Latinx participants in three U.S. urban areas (N = 1536) who were first (18%), second (60%), and third (22%) generation. In addition to demographics, measures included perceived cigarette availability and peer smoking, intentions and willingness to smoke, and general monitoring by parents. Parents reported on generational status and their own tobacco use. The primary outcome was participant's reported use of cigarettes. Results By 10th grade, 31% of Latinx youth had tried a cigarette, compared to 8% in 7th grade. After controlling for age, gender, and socioeconomic status, regression analyses indicated that there were no significant differences related to generational status in cigarette smoking initiation in either 7th or 10th grade. Youth tobacco-related perceptions, general parental monitoring, and parental tobacco use predicted Latinx adolescent cigarette use initiation by 10th grade. Conclusions Latinx adolescents might not have deferential smoking rates based on generation status, suggesting that the immigrant paradox concept may not hold for smoking initiation among Latinx adolescents. Rather, factors influencing cigarette initiation generally in adolescents as a group appear to apply to Latinxs as well.